Acute Kidney Injury in Pregnancies Complicated With Preeclampsia or HELLP Syndrome - Szczepanski, Jamie; Griffin, Ashley; Novotny, Sarah; Wallace, Kedra (Frontiers in Medicine, 2020)
Acute kidney injury that occurs during pregnancy or in the post-partum period (PR-AKI) is a serious obstetric complication with risk of significant associated maternal and fetal morbidity and mortality. Recent data indicates that the incidence of PR-AKI is increasing, although accurate calculation is limited by the lack of a uniform diagnostic criteria that is validated in pregnancy. Hypertensive disorders of pregnancy have been identified as major contributors to the burden of PR-AKI. As is now accepted regarding preeclampsia, it is believed that PR-AKI may have long-term renal, cardiovascular and neurocognitive consequences that persist far beyond the post-partum period. Further research regarding PR-AKI could be advanced by the development of a pregnancy-specific validated definition and classification system; and the establishment of refined animal models that would allow researchers to further elucidate the mechanisms and sequelae of the disorder.